(untitled) - Dutt, Sandeep (Dehra Dun, 1999)
This exclusive guide is for parents, teachers and students alike. In addition, it is a good resource for the schools too. Packed with valuable information and supported by educationists and the school community, it presents to the World, the top residential schools of India
Keywords: Boarding schools,Trường nội trú; Handbooks, manuals, etc.,Sổ tay, sách hướng dẫn, vv; India,Ấn Độ